Implementation of cyberlearning in elementary schools: case study in Indonesia - Jupriyanto, Jupriyanto; Prasetyo, Zuhdan Kun; Sujarwo, Sujarwo; Kusmaryono, Imam; Sari, Yunita (Journal of Education and Learning (EduLearn), 2025)
Many studies have focused on online learning in terms of it is structure and practice, but only some have sampled elementary school teachers. This article explains factor analysis of the relevance of online learning in Indonesia. They are taking teachers from 25 elementary schools with public, private, and Islamic school clusters. Data analysis found two groups of factors that determine online learning in elementary schools in Indonesia; the first is related to system quality and information quality, while the second is related to technology mastery, teacher characteristics, and student characteristics. Attention is focused on the readiness to transition from face-to-face learning to cyberlearning, which we wrote about in the learning recommendations. Overall, these two factors are related to implementing enjoyable online learning.